A Study on the Cyst-like Shadow in the Osteoarthritic Knee Joint - Taie, T.; Fukushima, M.; Osako, Y.; Kono, I.; Kamihira, M. (Orthopedics & Traumatology, 1974)
The cyst-like shadows are observed in 19 cases out of 823 cases of osteoarthritic knee joints roentgenographically. These cysts are located adjacent to the articular cartilage, most frequently in the medial femoral condyle and also in the medial tibial plateau. Such lesions are considered to be related to a increased stress through the closed side of the joint as in genu varus due to osteoarthritis. On histological examination of the 2 operated cases, the articular cartilage overlying the cyst is severely degenerated, and the inner wall of the cyst is lined by a thin layer of fibrous tissue containing both necrotic and newly-forming bone.